PELLET IKAN âLISA MUDARâ(LIMBAH PASAR MURAH DAN BERGIZI) OPTIMALISASI FUNGSI LIMBAH SAYURAN - Pratiwi, Trini Yuni; Maidah, Erika Nur; Ismail, Kadi Mey; Trapsilo, Priyandaru Agung Eko (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Feed is one of important thing in fish culture because its contribute about 60 % for production cost. To create a good and sustain fish culture, innovation of fish feed is needed. The feed should be economized, rich nutrition, and give optimum growth. One of that feed is Lisa Mudar, an innovative and organic feed which made from vegetables waste, sausage waste, fish flour, pollard, premix vitamin, adhesive flour, probiotic, and fish oil. Lisa Mudar has good nutrition that are protein 22 %, carbohydrats 27 %, lipid 3 %, and rude fiber 18,3 %. This feed can be used for catfish culture and also tilapia culture.Keyword: Pellet, Lisa Mudar, waste, vegetable, optimum